Os embargos à execução e a impugnação ao cumprimento de sentença do devedor solvente de quantia certa no novo Código de Processo Civil - Gomes, Ricardo Vick Fernandes (2016)
This work has as object the stay of execution and challenge to compliance with judgement of the solvent debtor of a determined amount and is justified by the entry into force, in the year 2016, of law n. 13.105/2015. It develops a study of these institutes detailing, when relevant, aspects related to their legal nature, hypothesis of use, inadmissibility and actions conditions, competence, terms and procedures, required warranties, suspensive effect, default hypothesis, judgment, legal fees and second phase stays of execution. It aims to find out how the new law regulated such institutes, what are the relevant changes from law n. 5.869/1973 and how those changes are expected to affect the civil process efficiency